(untitled) (Journal of the College of Basic Education, 2024)
In this study, the researcher seeks to shed light on the structural construction of sentences in Arabic proverbs, as proverbs represent one of the linguistic sources that are no less important in building linguistic wealth and formulating the linguistic system in all languages, not just Arabic. The proverb is a product of its environment, which reflects its linguistic and non-linguistic reality. The formal construction of sentences in Arabic proverbs varied in the structural sentence between the imperative and non-imperative construction, in a group of patterns. The imperative construction patterns had great fortunes in building the structural sentence of Arabic proverbs.